(−)-Epicatechin Reverses Glucose Intolerance in Rats Housed at Thermoneutrality - Chun, Ji Hye; Henckel, Melissa M.; Knaub, Leslie A.; Hull, Sara E.; Pott, Greg B.; Ramirez, David G.; Reusch, Jane E.-B.; Keller, Amy C. (Planta Medica, 2022)
Diabetes is a life-threatening and debilitating disease with pathological hallmarks, including glucose intolerance and insulin resistance. Plant compounds are a source of novel and effective therapeutics, and the flavonoid (−)-epicatechin, common to popular foods worldwide, has been shown to improve carbohydrate metabolism in both clinical studies and preclinical models. We hypothesized that (−)-epicatechin would alleviate thermoneutral housing-induced glucose intolerance. Male rats were housed at either thermoneutral (30 °C) or room temperature (24 °C) for 16 weeks and gavaged with either 1 mg/kg body weight or vehicle for the last 15 days before sacrifice. Rats housed at thermoneutrality had a significantly elevated serum glucose area under the curve (p < 0.05) and reduced glucose-mediated insulin secretion. In contrast, rats at thermoneutrality treated with (−)-epicatechin had improved glucose tolerance and increased insulin secretion (p < 0.05). Insulin tolerance tests revealed no differences in insulin sensitivity in any of the four groups. Pancreatic immunohistochemistry staining showed significantly greater islet insulin positive cells in animals housed at thermoneutrality. In conclusion, (−)-epicatechin improved carbohydrate tolerance via increased insulin secretion in response to glucose challenge without a change in insulin sensitivity.
Keywords: (−)-epicatechin; Theobroma cacao; Sterculiaceae; insulin secretion; glucose tolerance